Improvements in Endovascular Treatment for Acute Ischemic Stroke: A Longitudinal Study in the MR CLEAN Registry. Issue 6 (9th February 2022) - Compagne, Kars C.J.; Kappelhof, Manon; Hinsenveld, Wouter H.; Brouwer, Josje; Goldhoorn, Robert-Jan B.; Uyttenboogaart, Maarten; Bokkers, Reinoud P.H.; Schonewille, Wouter J.; Martens, Jasper M.; Hofmeijer, Jeannette; van der Worp, H. Bart; Lo, Rob T.H.; et al.
Abstract : Background: We evaluated data from all patients in the Netherlands who underwent endovascular treatment for acute ischemic stroke in the past 3.5 years, to identify nationwide trends in time to treatment and procedural success, and assess their effect on clinical outcomes. Methods: We included patients with proximal occlusions of the anterior circulation from the second and first cohorts of the MR CLEAN (Multicenter Randomized Clinical trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands) Registry (March 2014 to June 2016; June 2016 to November 2017, respectively). We compared workflow times and rates of successful reperfusion (defined as an extended Thrombolysis in Cerebral Infarction score of 2B-3) between cohorts and chronological quartiles (all included patients stratified in chronological quartiles of intervention dates to create equally sized groups over the study period). Multivariable ordinal logistic regression was used to assess differences in the primary outcome (ordinal modified Rankin Scale at 90 days). Results: Baseline characteristics were similar between cohorts (second cohort n=1692, first cohort n=1488) except for higher age, poorer collaterals, and less signs of early ischemia on computed tomography in the second cohort. Time from stroke onset to groin puncture and reperfusion were shorter in the second cohort (median 185 versus 210 minutes; P <0.001 and 236 versus 270 minutes; P <0.001, respectively). Successful reperfusion was achieved more often in the second than in the first cohort (72% versus 66%; P <0.001). Functional outcome significantly improved (adjusted common odds ratio 1.23 [95% CI, 1.07–1.40]). This effect was attenuated by adjustment for time from onset to reperfusion (adjusted common odds ratio, 1.12 [95% CI, 0.98–1.28]) and successful reperfusion (adjusted common odds ratio, 1.13 [95% CI, 0.99–1.30]). Outcomes were consistent in the analysis per chronological quartile. Conclusions: Clinical outcomes after endovascular treatment for acute ischemic stroke in routine clinical practice have improved over the past years, likely resulting from improved workflow times and higher successful reperfusion rates.